Electrical impedance tomography reveals pathophysiology of neonatal pneumothorax during NAVA. Issue 8 (24th May 2020) - Kallio, Merja; Rahtu, Marika; van Kaam, Anton H.; Bayford, Richard; Rimensberger, Peter C.; Frerichs, Inéz
Abstract: Pneumothorax is a potentially life‐threatening complication of neonatal respiratory distress syndrome (RDS). We describe a case of a tension pneumothorax that occurred during neurally adjusted ventilatory assist (NAVA) in a preterm infant suffering from RDS. The infant was included in a multicenter study examining the role of electrical impedance tomography (EIT) in intensive care and therefore continuously monitored with this imaging method. The attending physicians were blinded for EIT findings but offline analysis revealed the potential of EIT to clarify the underlying cause of this complication, which in this case was heterogeneous lung disease resulting in uneven ventilation distribution. Instantaneous increase in end‐expiratory lung impedance on the affected side was observed at time of the air leak. Real‐time bedside availability of EIT data could have modified the treatment decisions made. Abstract : Real‐time bedside availability of EIT for continuous monitoring of aeration and ventilation distribution in neonatal RDS might help to recognize patients at risk of complications, allow timely treatment decisions and early detection of undesired events.